CARCASSES PRODUCTION OF WHITE GOLD CROSSBRED CHIKEN WITH LANCY FEED DRAGON FRUIT PEEL JUICE (Hylocereus sp) THROUGHT DRINKING WATER - N.P.P., Anestika; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika, 2020)
This study aims to examine the weight and cut carcasses of White Gold X Lancy crossbreed chickens fed dragon fruit skin juice through drinking water. Has been carried out in a breeder's cage located on Jalan Cekomaria, Peguyangan, Banjar Kedua, Denpasar. For 8 weeks. The study was carried out using a Completely Randomized Design (CRD) consisting of four treatments, namely: R0: Without administration of dragon fruit skin juice through drinking water, R1: Addition of 5% dragon fruit skin juice through drinking water, R2: Addition of 10% skin juice dragon fruit through drinking water and R3: Addition of 15% dragon fruit skin juice through drinking water. The observed variables were cutting weight, carcass weight, carcass percentage, chest weight, thigh, wing, and back. The results showed that the treatment of R1, R2 and R3 were 5.64%, 8.20% and 8.87% respectively (P <0.05) than R0 (control). Whereas the R1 treatment was 2.77% lower than R2 (P> 0.05) in chest weight. Based on the results of the study it can be concluded that the administration of dragon fruit skin juice as much as 5%, 10% and 15% affect the weight of the chest, thighs and percentage of carcass, but it does not affect the cutting weight, carcass weight, wings and back of the chicken crossing White Gold X Lancy age 14 weeks. Key words : dragon fruit skin juice, carcass, carcass fracture, crossbred chicken